Weather factors affecting snow coverage on Mt. Jayawijaya, Indonesia - Syamsinar; Halide, Halmar; Febrianti, Aini Suci; Laode, Andri Moh Wahyu (Journal of Degraded and Mining Lands Management, 2025)
The snow cover in Jayawijaya, Papua, Indonesia, has been rapidly declining due to various climatic factors, posing significant threats to both the ecosystem and local culture. This research focused on the analysis of the impact of weather factors (temperature, relative humidity, wind direction, and wind speed) on the decrease in snow cover in Mt. Jayawijaya. Using the datasets from 2013 to 2022, a stepwise multiple regression analysis was performed to ascertain the predictors for snow cover loss. The findings indicated that out of all the weather factors, relative humidity and wind direction were the most important, with a p-value of 0.005 and 0.032, respectively. The regression model indicates that higher humidity increases snow sublimation, while wind direction brings warm air that accelerates snow melting. Pearson correlation analysis showed a strong correlation (r = 0.81) between the observed snow cover decline and the model, with an RMSE of 20.70 ha. These findings contribute to the understanding of how atmospheric factors interact with snow dynamics in tropical regions and can aid in future conservation efforts for Jayawijaya’s snow cover.